2018
DOI: 10.1002/esp.4462
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cliff retreat in coastal Quaternary sediments using anatomical changes in exposed tree roots

Abstract: Sea cliffs represent 80% of the world's coasts and can be found virtually in all types of morphogenetic environments. Most studies on rocky environments focused on the impacts of modern sea level rise on cliff stability derived from sequential surveys, direct measurements or erosional features in anthropogenic structures. In this study, we explore the potential of dendrogeomorphic techniques to quantify multidecadal changes in coastal environments on Porquerolles Island (France). We sampled a total of 56 cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 97 publications
0
1
0
1
Order By: Relevance
“…No geral, a taxa média de retração para o litoral do Município de Tibau do Sul entre 2003 e 2013 foi de -0,442 m/ano, assinalando que 37% de linhas de costa distintas por falésias marinhas esteve submetida a erosão. Em comparação a alguns estudos recentes, similares na abordagem metodológica e nas análises de curto prazo temporal, destaca-se como taxa de recuo expressivamente alta, a exemplo da costa sul e central da Califórnia (EUA) com -0,044 m/ano (YOUNG, 2018), e de setores da costa francesa com recuo de -0,060m/ano a -0,390 m/ano (LOPEZ-SAEZ et al, 2018).…”
Section: Resultados E Discussõesunclassified
“…No geral, a taxa média de retração para o litoral do Município de Tibau do Sul entre 2003 e 2013 foi de -0,442 m/ano, assinalando que 37% de linhas de costa distintas por falésias marinhas esteve submetida a erosão. Em comparação a alguns estudos recentes, similares na abordagem metodológica e nas análises de curto prazo temporal, destaca-se como taxa de recuo expressivamente alta, a exemplo da costa sul e central da Califórnia (EUA) com -0,044 m/ano (YOUNG, 2018), e de setores da costa francesa com recuo de -0,060m/ano a -0,390 m/ano (LOPEZ-SAEZ et al, 2018).…”
Section: Resultados E Discussõesunclassified
“…Cliff retreat rates in coastal regions are well characterized and studied in part due to higher population density [3][4][5][6][7], but cliff retreat rates in arid environments are less thoroughly studied [8,9]. Existing and proposed waste disposal facility locations in the southwestern and western U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, long-term measurement data on sea cliff erosion distances have accumulated (Young et al, 2020). Therefore, most studies on coastal wave erosion focus on establishing the time equation of the sea cliff erosion rate, which primarily includes the fixed value method (Lopez-Saez et al 2018) and probability methods (Muñoz et al 2020). Some studies, such as Huppert et al (2020), that focused on studying the erosion mechanism of wave erosion coast found a positive correlation between wave energy and rocky sea cliff erosion and 4 constructed an energy prediction equation for sea cliff erosion.…”
Section: Introductionmentioning
confidence: 99%